PTU-066 A Model To Assess The Cost Of Flare In Ulcerative Colitis (uc) To The Nhs. (9th June 2014) - Bassi, A; Tolley, K; Wiseman, G; Shaw, S
Abstract : Introduction: Disease flare in ulcerative colitis (UC) can result in substantial cost implications to the NHS. While the costs associated with treatment and management of UC are well-documented, estimates of the cost of flare are lacking. A cost analysis was performed to construct a model to estimate the costs associated with managing a flare across variable pathways. Methods: A decision tree model was developed in Excel to estimate the direct medical costs of flares of various clinical severity. Within the model, the baseline UC patient cohort was maintained on Asacol ® (mesalazine) at a maximum dose of 2.4 g/day. Simplified care pathways were mapped, assuming that patients would either be treated and managed in primary care, or as an outpatient, or admitted to hospital. Taking a conservative approach, costs for surgery and other procedures e.g., stoma care were excluded as these outcomes are rare and inclusion would significantly increase average flare cost estimates. Treatment and management strategies were based on best practice guidelines, published data sources and clinical expert opinion. Drug costs were calculated using the British National Formulary (BNF) and healthcare management costs were based on published unit costs. The relative proportions of patients likely to follow each route of the treatment pathway were estimated and weightings were applied to enable calculation of an average cost of flare. Results: The estimated annual cost to manage a patient with UC in remission was £955. The estimated cost to control a flare in primary care was £175 and for secondary care outpatient management was £578. For secondary care inpatient management, the estimated cost was £3488. If a biologic/ciclosporin was needed, the estimated cost rose to £4272. All costs were inclusive of clinical investigations and treatment reviews. The proportions of patients managed via each pathway were applied to calculations resulting in an estimated average cost of flare of £984. Conclusion: A model was developed, based on simplified decision tree pathways to enable estimation of the cost of flare in UC. Depending on the severity of the flare episode, costs ranged from £175 to £4272. In the future, this model can be used for economic evaluations of interventions to reduce the risk of flare in UC and to help understand the costly aspects of managing ulcerative colitis. Disclosure of Interest: A. Bassi Speaker bureau with: Warner Chilcott (UK) Ltd, K. Tolley Consultant for: Warner Chilcott (UK) Ltd, G. Wiseman Employee of: Warner Chilcott (UK) Ltd, S. Shaw Consultant for: Warner Chilcott (UK) Ltd.